Max Scheler’s influence on Kurt Schneider: $hJohn Cutting, Maria Mouratidou, Thomas Fuchs, Gareth Owen - Cutting, John; Mouratidou, Maria; Fuchs, Thomas; Owen, Gareth (History of psychiatry, 2016)
Kurt Schneider (1887-1967) met Max Scheler (1874-1928) in 1919 when he enrolled in the latter’s philosophy seminars at the University of Cologne. Kurt Schneider...
Gesehen am 05.05.2020